Legume rotation in the moist tropical savanna: managing soil nitrogen dynamics and cereal yields in farmers' fields - Oikeh, S.; Chude, V.; Carsky, R.J.; Weber, G.; Horst, W. (Cambridge University Press, 1998)
The contribution of root and leaf litter to soil nitrogen dynamics, nitrogen uptake and balance was evaluated under cereal–legume rotations in a tropical moist savanna soil. Two legumes, soyabean (Glycine max) and stylo (Stylosanthes hamata), and maize (Zea mays) as a control were grown in four farmers' fields of different native fertility in 1993. At the end of the season, soyabean grain and stover were harvested and stylo biomass was removed for fodder. At the beginning of the 1994 season levels of total mineral nitrogen at a soil depth of 0–30 cm were 75, 52 and 44 kg ha−1 following soyabean, stylo and maize respectively. Total nitrogen uptake by maize was over 25% higher following legumes than following maize. Maize yield was 20 and 24% higher when grown after stylo and soyabean than after maize in spite of the removal of the standing legume biomass from the plots. Sorghum grain yield and nitrogen uptake were not significantly affected by the previous crops. Nitrogen balance estimates indicated that loss of nitrogen, probably due to leaching, was lowest in the plots previously planted with stylo. Results indicated opportunities to integrate appropriate legume-based technologies into the farming systems based on an identification of inherent nitrogen-release patterns.